EFEKTIVITAS PENYULUHAN KESEHATAN TERHADAP SIKAP REMAJA DALAM MENCEGAH PENYALAHGUNAAN NARKOTIKA, PSIKOTROPIKA DAN ZAT ADIKTIF - Muriyati; A.Nurlaela Amin (Jurnal Kesehatan Panrita Husada, 1970)
Drug abuse is a global public health problem that must receive important attention from all parties. This is due to the prevalence of drug abuse in the world increases every year. According to the results of a survey conducted by researchers, information was obtained that in the Kasimpureng Kelurahan which is located in the city of Bulukumba is often the target and target of arrest for drug dealers and drug users. In the area where the researcher is located in the Kasimpureng area with a high level of drug abuse and illicit trafficking. Therefore special attention is needed for adolescents who are at risk of drug abuse to have good knowledge and attitude about drug abuse behavior. The purpose of this study is to determine the effectiveness of health education on adolescent attitudes in preventing drug abuse in Kasimpureng Sub-district, Ujung Bulu District Bulukumba. This type of research uses quasi-experimental research with a nonrandomized pretest-posttest with control group design. The sample in this study were 36 respondents, in which the sample in this study was divided into 2 groups, 18 respondents for the control group and 18 respondents for the experimental group taken employing consecutive sampling. Analysis of data and research using Wilcoxon test statistical tests. The results of the analysis used Wilcoxon statistical test with a confidence level (α = 0.05). Based on the results of this test, the value of p is 0.012, thus p <α (0.012 <0.05). Then H0 is rejected and Ha is accepted. The conclusion of this study is the effectiveness of health education on adolescent attitudes in preventing the abuse of psychotropic narcotics and addictive substances (Drug) in Kel. Kasimpureng Kec. Ujung Bulu Kab. Bulukumba.